2016
DOI: 10.1177/0194599816629378
|View full text |Cite
|
Sign up to set email alerts
|

Sino‐Nasal Outcome Test–22

Abstract: The Hebrew version of SNOT-22 questionnaire is a valid outcome measure for patients with CRS with or without nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The sample size was relatively small, but comparable with average numbers of other international SNOT-22 validation studies. 6 8 , 10 , 11 , 18 , 21 Furthermore, validation of the SNOT-22 in the current study was in a Saudi Arabian population. We did not enroll subjects from other Arab countries.…”
Section: Discussionmentioning
confidence: 73%
“…The sample size was relatively small, but comparable with average numbers of other international SNOT-22 validation studies. 6 8 , 10 , 11 , 18 , 21 Furthermore, validation of the SNOT-22 in the current study was in a Saudi Arabian population. We did not enroll subjects from other Arab countries.…”
Section: Discussionmentioning
confidence: 73%
“…We used the validated Hebrew version of the Sinonasal Outcome Test-22 to study different mask types' impact. This questionnaire addresses various aspects directly related to specific diseases of the nose and sinuses, as well as general health [6]. Previous studies have confirmed that the SNOT-22 is valid and reliable for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire has been validated to evaluate the outcome after endoscopic sinus surgery (ESS) in CRS patients and has been used to evaluate the effect of ESS in CF patients 23,24 . Recently, it was translated to Hebrew and validated 25 …”
Section: Methodsmentioning
confidence: 99%